Five new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from Vietnam - Nie, Lei; Yao, Zhiyuan; Pham, Dinh-Sac; Li, Shuqiang (Zootaxa, 2018)
Five new species of the genus Khorata Huber, 2005 are reported from Vietnam: Khorata bachma Yao & Li sp. nov. (Thua Thien-Hue), K. cucphuong Yao & Li sp. nov. (Ninh Binh), K. vinhphuc Yao & Li sp. nov. (Vinh Phuc), K. palace Yao & Li sp. nov. (Ninh Binh) and K. quangbinh Yao & Li sp. nov. (Quang Binh). Type material is deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing, China.